Allelic Variants Within the ABO Blood Group Phenotype Confer Protection Against Critical COVID-19 Hospital Presentation - Herbert F. Jelinek; Herbert F. Jelinek; Herbert F. Jelinek; Mira Mousa; Mira Mousa; Nawal Alkaabi; Eman Alefishat; Eman Alefishat; Gihan Daw Elbait; Hussein Kannout; Hiba AlHumaidan; Francis Amirtharaj Selvaraj; et al. (Frontiers in Medicine, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) disease severity differs widely due to numerous factors including ABO gene-derived susceptibility or resistance. The objective of this study was to investigate the association of the ABO blood group and genetic variations of the ABO gene with COVID-19 severity in a heterogeneous hospital population sample from the United Arab Emirates, with the use of an epidemiological and candidate gene approach from a genome-wide association study (GWAS).Methods: In this cross-sectional study, a total of 646 participants who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were recruited from multiple hospitals and population-based (quarantine camps) recruitment sites from March 2020 to February 2021. The participants were divided into two groups based on the severity of COVID-19: noncritical (n = 453) and critical [intensive care unit (ICU) patients] (n = 193), as per the COVID-19 Reporting and Data System (CO-RADS) classification. The multivariate logistic regression analysis demonstrated the association of ABO blood type as well as circulating anti-A antibodies and anti-B antibodies as well as A and B antigens, in association with critical COVID-19 hospital presentation. A candidate gene analysis approach was conducted from a GWAS where we examined 240 single nucleotide polymorphisms (SNPs) (position in chr9: 136125788-136150617) in the ABO gene, in association with critical COVID-19 hospital presentation.Results: Patients with blood group O [odds ratio (OR): 0.51 (0.33, 0.79); p = 0.003] were less likely to develop critical COVID-19 symptoms. Eight alleles have been identified to be associated with a protective effect of blood group O in ABO 3'untranslated region (UTR): rs199969472 (p = 0.0052), rs34266669 (p = 0.0052), rs76700116 (p = 0.0052), rs7849280 (p = 0.0052), rs34039247 (p = 0.0104), rs10901251 (p = 0.0165), rs9411475 (p = 0.0377), and rs13291798 (p = 0.0377).Conclusion: Our findings suggest that there are novel allelic variants that link genetic variants of the ABO gene and ABO blood groups contributing to the reduced risk of critical COVID-19 disease. This study is the first study to combine genetic and serological evidence of the involvement of the ABO blood groups and the ABO gene allelic associations with COVID-19 severity within the Middle Eastern population.